A political & religious history of Bhutan, 1651-1906 - Dorji, C. T. (Thimp[h]u : Sangay Xam in collaboration with Prominent Publishers, Delhi, India, 1995)
Chiefly covers the period from early to 1906.
Includes bibliographical references in index.
Keywords: Bhutan -- History; Bhutan -- Religion